An observational post-authorization study to assess the effectiveness of a single dose Ad26.COV2.S for the prevention of COVID-19 using real-world data - Boehme, Amelia; Harvey, Raymond A.; Madsen, Ann; Rubens, Lexie; Toyip, Astra; Batech, Michael; Ricci, Deborah; Nyaku, Mawuli (Frontiers in Public Health, 2024)
BackgroundThe goal of this FDA-committed, post authorization study was to assess the real-world effectiveness of Ad26.COV2.S in preventing observed COVID-19 disease in individuals in the United States interacting with the healthcare system who were vaccinated according to the national immunization recommendations.MethodsThe study cohort consisted of individuals ≥18 years in the U.S. between March 1, 2021 and July 31, 2022. Two exposure groups were considered: those who received a single dose of COVID-19 Ad26.COV2.S vaccine and individuals who were unvaccinated. Individuals eligible for the referent group, defined as those who were unvaccinated, were identified through exact matching on age, sex, location, and Gagne comorbidity score. Propensity-score (PS) matched Cox proportional hazards models were used to evaluate COVID-19 related outcomes.ResultsA total of 478,162 vaccinated, and 1,897,759 risk set sampled (RSS) and PS-matched unvaccinated referent individuals were included. The vaccine effectiveness (VE) against any observed COVID-19 disease was 20% (95% CI, 19 to 21%). VE increased as the outcome severity increased. The VE against COVID-19 related hospitalizations was 43% (95% CI, 40 to 45%). VE was highest, 53% (95% CI, 42 to 61%), against all-cause mortality temporally associated with COVID-19. The results of subgroup analyses generally showed a similar pattern as the main analyses with VE increasing in parallel with seriousness of outcomes, albeit with lower VE in groups thought to be at higher risk of COVID-19.DiscussionThis population-representative cohort study in U.S. clinical practice showed that a single dose of Ad26.COV2.S is effective for at least 12 months against several COVID-19 related outcomes. Individuals who were vaccinated with a single dose of Ad26.COV2.S were at lower risk for developing COVID-19, for being hospitalized for COVID-19, and for all-cause mortality temporally associated with COVID-19 compared to unvaccinated individuals in the U.S. during Alpha, Delta, and Omicron BA.1, BA.2, BA.212.1, and BA.5 variants circulation.